Performance evaluation of alumina-graphene hybrid nano-cutting fluid in hard turning - Singh, R.; Sharma, A.; Dixit, A.; Tiwari, A.; Pramanik, Alokesh; Mandal, A. (Elsevier, 2017)
A hybrid nanofluid (NF) with better thermal and tribological properties has been developed in this investigation by mixing alumina-based nanofluid with graphene nanoplatelets (GnP) in the volumetric concentrations of 0.25, 0.75 and 1.25 vol %. It was noted that an increase of nanoparticle concentration enhances both, the thermal conductivity and viscosity, though the hybrid nanofluid has lower thermal conductivity compare to its constituents and the viscosity lies in between its constituents. The tribological test confirms that the wear decreases with the increase of nanoparticle concentration and the hybrid nanofluid generated least amount of wear. Hybrid nanofluid shows better wettability results as compared to alumina-based nanofluid as well as base fluid. The turning of AISI 304 steel under minimum quantity lubrication (MQL) technique clearly establishes that application of hybrid nanofluid performs better as compared to alumina nanoparticle mixed cutting fluid. The study reveals that blending of GnP with alumina enhances the performance of hybrid nanofluids. The application of hybrid nanofluid with MQL significantly reduces the surface roughness by 20.28% and cutting force, thrust force and feed force by 9.94%, 17.38% and 7.25%, respectively.